Publications - Laszlo, J.
Publikationen des Wissenschaftlers Joe Laszlo: Joseph F. Laszlo, M. van de Panne, and E. Fiume. Limit Cycle Control and its Application to the Animation of Balancing and Walking. Proceedings of SIGGRAPH 96 (New Orleans, August, 1996). In ACM SIGGRAPH, pp. 155-162. Joseph F. Laszlo. Controlling Bipedal Locomotion for Computer Animation. 1996 M.A.Sc. Thesis, University of Toronto.Refereed Conferences and Workshops Shahzad Malik, Joe Laszlo. "Visual Touchpad: A Two-handed Gestural Input Device". To appear in Proceedings of International Conference on Multimodal Interfaces (ICMI) 2004, State College, PA, USA. (see http://www.cs.toronto.edu/~smalik/http://www.cs.toronto.edu/~smalik/academics.html)